Pleiotropic Effects of PCSK9 Inhibitors on Cardio-Cerebrovascular Diseases - Zhenzhen Li; Lin Zhu; Yeqiong Xu; Yiting Zhang; Yukai Liu; Huiling Sun; Shuo Li; Meng Wang; Teng Jiang; Junshan Zhou; Qiwen Deng (Biomedicines)
Cardiovascular disease (CVD) and ischemic stroke (IS) are the primary causes of mortality worldwide. Hypercholesterolemia has been recognized as an independent risk factor for CVD and IS. Numerous clinical trials have unequivocally demonstrated that reducing levels of low-density lipoprotein cholesterol (LDL-C) significantly mitigates the risk of both cardiac and cerebral vascular events, thereby enhancing patient prognosis. Consequently, LDL-C reduction remains a pivotal therapeutic strategy for CVD and IS. However, despite intensive statin therapy, a significant proportion of high-risk hypercholesterolemic patients fail to achieve sufficient reductions in LDL-C levels. In response to this challenge, an inhibitor targeting proprotein convertase subtilisin-kexin type 9 (PCSK9) has been developed as a therapeutic intervention for hyperlipidemia. Numerous randomized controlled trials (RCTs) have conclusively demonstrated that the combination of PCSK9 inhibitors and statins significantly enhances prognosis not only in patients with CVD, but also in those afflicted with symptomatic intracranial artery stenosis (sICAS). PCSK9 inhibitors significantly reduce LDL-C levels by binding to the PCSK9 molecule and preventing its interaction with LDLRs. This prevents degradation of the receptor and increases uptake of LDL-C, thereby decreasing its concentration in blood. Besides significantly reducing LDL-C levels, PCSK9 inhibitors also demonstrate anti-inflammatory and anti-atherosclerotic properties while promoting plaque stabilization and inhibiting platelet aggregation and thrombosis. This article aims to provide a comprehensive review based on the relevant literature regarding the evolving understanding of pleiotropic effects associated with PCSK9 inhibitors, particularly focusing on their impact on the cardiovascular system and central nervous system.